Factors Associated with Delayed Diagnosis among Tuberculosis Patient in Kebumen District - Edwin Sovvan Aritonang; Ning Rintiswati; Riris Andono Ahmad (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: Tuberculosis is a major global health problem. It is estimated that almost 9 million new cases detected in 2011 and 1.4 million died because of TB. Early diagnosis and effective treatment are the key elements of the TB control program. Delayed diagnosis associated with a longer duration of infectiousness, increase the severity of the disease, more severe complication and even death.Objectives: To determine the factors associated with delayed diagnosis among tuberculosis patients in Kebumen District.Methods : A cross sectional study among newly diagnosed TB patients in April to June 2013 in Kebumen was conducted. The data was collected using a questionnaire interviewing officers of government health care facilities which have implemented DOTS programs already. Data was analyzed by a logistic regression test with confidence interval (CI) of 95%.Results: Eighty five pulmonary TB patients were studied consisting of 65 TB smear positive and 20 smear negative/roentgen positive patients. The median duration of delayed patients was 3.9 weeks; delayed health service was 2.6 weeks and delayed diagnosis was 7.6 weeks. Multivariate analysis showed that factors associated with delayed diagnosis were the type of health services which first visited (p value = 0.002 and OR = 6.87), level of knowledge about TB (p value = 0.002 and OR = 6.41), educational level (p value = 0.024 and OR = 5.68) and the number of visits to health service (p value = 0.021 and OR = 3.87).Conclusion : The median duration of delayed diagnosis was 7.6 weeks. Delayed diagnosis among TB patients in Kebumen Distict was associated with type of health services which is non-DOTS, low level of knowledge about TB,  low levels of education and the number of visits to health services ≥3 times.Keywords: delayed diagnosis, TB patients, Kebumen District